Kiedy żył św. Patryk? Rozważania nad chronologią życia Apostoła Irlandii - Kaźmierczak, Małgorzata (Vox Patrum, 2004)
The author of the article analyzes all theories on the chronology of St. Patrick's life - his birth date, the date of his coming to Ireland as a bishop, and his death. As there are two dates of his death mentioned in the Irish Annals: 461 and 493, the issue has been controversial, although traditional historiography assumes the second date is false. The author presents all the theories that arouse since the early forties when Thomas Francis O’Rahilly came up with the theory about the existence of two Patricks: Patrick Palladius (who came to Ireland in 431) and Patrick Briton. The traditional version, which is the only accepted by Polish historians, does not take into consideration the accounts of Prosper of Aquitaine and the time when these texts were written, and ignores the fact that the death of one of St. Patrick's disciples was mentioned in 535 or 537. The author presents her own version of events based on the above mentioned facts and the sentence found in the Irish Annals of Ulster under the year 553, that the relics of St. Patrick were translated after 60 years from his death by Colum Cille, indicating that the later date of his death is actually true. Finaly, the author suggests, that the date of St. Patrick's coming to Ireland in 432 was the date of his first coming to Ireland, as a slave rather than a bishop.